Periovulatory steroid hormone profile in relation to superovulatory responses in native Ongole cows - RAO, M MUTHA; MAHESH, Y UMA; RAO, K BABU (The Indian Journal of Animal Reproduction, 2023)
Plasma progesterone (P4) and 17-IJ estradiol (E2) concentrations were estimated and correlated wilh ovulatory response,tolal and viable embryo recovery rales in six Ongole cows (Bo$ indicu$) superovulatcd during mid luteal phase (day 10-11) of lheestrus cycle using FSH. The mean P4 and E2 levels on the day of superovulation were found to be 1.45 ng/ml and 37.83 pg/mlrespectively. No correlations were observed between plasma P4 levels on day-4 and ovulatory response or between plasma E2 on day·o• and CL response. Positive correlations were observed between plasma P4 levels starting from day 3 to 7 and superovulatoryresponses (number of palpated CL, mean total and viable embryos). However, a negative correlation was observed between E2 onday-4 and ovulatory resonse. Determination of plasma P4 and E2 levels before, during and after ovarian super stimulation may helpin predicting ovulatory response, total and viable embryo recovery in Ongole cows.
Keywords: Progesterone; 17-IJ estradiol; Ongole; embryo